Prevalensi Kekerasan Terhadap Perawat Di Tempat Kerja Di Rumah Sakit Ditinjau Dari Berbagai Negara Di Dunia : A Literature Review - Kadir, Abd; Syahrul, Syahrul; Erika, Kadek Ayu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background : Workplace violence in health sector has turned an alarming concern worlwide in this era. Nowadays, working violence toward health service personnels, particularly the nurses becomes a significant issue in all of health care centres in the world. The International Labor Organization (ILO) reported that nurses are facing more various kinds of working violences than other health sector personnels. On average, the nurses’ position is three times more risky than the other job positions to experience working violence. The prevalence of violence varies according to its countries and labour regulations.Purpose: The purpose of this literature review was to know the prevalence rate of working violence occuring in medical centres or hospitals according to various different countries’ perspectives.Method: The data bases which were used to collect information and write up the literature review were Pubmed, Proquest, and Google Scholar, Science Direct. Result: There were 40 relevant articles identified and issued from 2013 to 2018, in which 30 of those articles meet the inclusive criteria. The result of the study shows that there are 4 kinds of working violence which have occured, including physical iolence with 7.5% (in Kongo) - 81.9% (in China), psychological violence with 6.5% (in Slovenia) - 89.58% (in South Euthopia), sexual harrasment with rate of 1.1% (in Hongkong) - 17,9% (in Slovenia) and racial harrasment with percentage of 2.6% (in Hongkong) and 3% (in Malawi). Conclusion: The prevalence of working violence in hospitals is categorized into physical violence, psychological violence, sexual and racial harrasment which predominantly take place in all of the hospital room sectors, starting from the outpatient care rooms to the emergency rooms. It is important that policies be issued to overcome the problem and to help nurses who experienced working violence in hospitals so as not to intrude on their work performance and services to patients.